Design of parabolic solar dish tracking system using arduino - Asif Ahmed Rahimoon; Mohd Noor Abdullah; Dur Muhammad Soomro; Murad Yahya Nassar; Z.A. Memon; P.H. Shaikh (Institute of Advanced Engineering and Science, 2020)
This paper demonstrates the designing parameters of a solar parabolic dish prototype for rustic areas with great solar irradiance rate availability, where have no access of electricity services or low-income people survives to buy a stove (electric or gas). The solar parabolic dish prototype intends a solution against these types of remedies and pursues solar light to work. The parabolic dish has a polished surface, where the solar radiations fall and collected at a single concentrated focal point. At this point the collected form of energy is used to derive different thermal applications like as; cooking & heating with single and dual axis schemes. This paper discusses the important stages of dual axis prototype; implementation, solar location strategy, the analysis in terms of theory, structural design & material. The dual axis prototype is implemented through the help of Arduino chipboard that is easily in maintenance, along with that this prototype is configured with anti-lock H-bridge (L298) module to overcome the control circuit complexity and AVR modules. Two rotational motors of 12V are installed on 4*4ft designed aluminum frame with a dual-axis tracking system. The jerks among trackers are also reduced with this prototype which maintains the experimental declination angle about .To finish, this paper results that parabolic solar dish tracker obtains 3.43% improved power efficiency in comparison of photovoltaic panel tracker.